Improvement on Bill of Materials Formatting Process by Adopting Lean and Six Sigma Approaches - A Case Study in a Semiconductor Industry - Ahmad, Rosmaini; Abd Wahab, Ilhammee; Mustafa, Shaliza Azreen; Jusoh, Muhammad Shahar; Hj Din, Mohd Salleh (International Journal of Integrated Engineering, 2019)
This paper present an improvement project for the case of Bill of Materials (BOM) formatting process by adopting Lean and Six Sigma approaches. Currently, BOM formatting process involved repetitive tasks, where many of manual touches (manual computer mouse clicks), thus consumed a significant amount of time. The focus of Lean approach in this project is to identify and analyze the related wastes in the current BOM formatting process.  Several Lean tools are applied such as, Root Cause, Five Whys analysis and Value Stream Mapping (VSM) concept to analyze the problem. Six Sigma approach plays an important role to systematically carry out the improvement project based on it well known method called; Define, Measure, Analyze, Improve and Control (DMAIC). This paper gives an insight that the right application of Lean and Six Sigma approaches will significantly helped an organization to achieve operational excellence, where in this project it happens at BOM formatting process. Through this project, the case study company has improved (reducing) the BOM processing time from average 50 to 5 minutes, while manual touches reduced from 290 to 30 touches only. Furthermore, elimination of these wastes (waiting and motion) has increase work efficiency and contributes to a significant financial savings to $1680 per month.